Effect of acids and alkalis on the resistance of a polypropylene geotextile against thermo-oxidation - Maria de Lurdes Lopes (2019)
The long-term behaviour of geosynthetics is one of the most important topics in the research about these materials. This work studies the effect of some liquids (water, sulphuric acid 0.1 mol.L-1 and sodium hydroxide 0.1 mol.L-1) in the resistance of a polypropylene geotextile against thermo-oxidation. For that purpose, the geotextile was (1) exposed in isolation to the liquids (immersion tests) and to thermo-oxidation (oven-ageing tests) and (2) exposed consecutively to both degradation tests (combined effect). The damage suffered by the geotextile in the degradation tests was evaluated by monitoring changes in its tensile behaviour. Based on the changes occurred in tensile strength, reduction factors were determined. The reduction factors obtained in the successive exposures to liquids and thermo-oxidation were compared with the reduction factors determined by the traditional methodology for the combined effect of those agents. The results, among other findings, showed the existence of an effect of sulphuric acid 0.1 mol.L-1 in the resistance of the geotextile against thermo-oxidation. Indeed, the successive exposure to sulphuric acid 0.1 mol.L-1 and thermo-oxidation (two agents that individually did not cause relevant damage) led to some degradation. Due to the interaction occurred between the degradation agents, the traditional methodology was unable to predict correctly (by underestimating) the reduction factor for the combined effect of sulphuric acid 0.1 mol.L-1 and thermo-oxidation.